The initial effects of microclimate and invertebrate exclusion on multi-site variation in the mass loss of temperate pine and oak deadwoods - Seongjun Kim; Seung Hyun Han; Guanlin Li; Yujin Roh; Hyun-Jun Kim; Yowhan Son (Scientific Reports, 2021)
Abstract Quantifying deadwood decomposition is prioritized by forest ecologists; nonetheless, uncertainties remain for its regional variation. This study tracked variations in deadwood decomposition of Korean red pine and sawtooth oak in three environmentally different regions of the Republic of Korea, namely western, eastern, and southern regions. After 24 months, dead pine and oak woods lost 47.3 ± 2.8% and 23.5 ± 1.6% in the southern region, 13.3 ± 2.6% and 20.2 ± 2.8% in the western region, and 11.9 ± 7.9% and 13.9 ± 2.3% in the eastern region, respectively. The regional variation in the decomposition rate was significant only for dead pine woods (P < 0.05). Invertebrate exclusion treatment reduced the decomposition rate in all region, and had the greatest effect in the southern region where warmer climate and concentrated termite colonization occurred. The strongest influential factor for the decomposition of dead pine woods was invertebrate exclusion (path coefficient: 0.63). Contrastingly, the decomposition of dead oak woods was highly controlled by air temperature (path coefficient: 0.88), without significant effect of invertebrate exclusion. These findings reflect the divergence in regional variation of deadwood decomposition between pine and oak, which might result from the different sensitivity to microclimate and decomposer invertebrates.